Medullary thyroid carcinoma in children - Niedziela, Marek; Bręborowicz, Danuta; Kulińska-Niedziela, Izabela; Bręborowicz, Jan; Maceluch, Jarosław; Korman, Eugeniusz (Contemporary Oncology/Współczesna Onkologia, 2005)
The vast majority of thyroid carcinomas are sporadic. Medullary thyroid carcinoma (MTC) is the common hereditary form of thyroid carcinoma (25% in the group of medullary thyroid carcinomas). This paper describes the current view on clinical presentation of medullary thyroid carcinoma in children, diagnostic and therapeutic management and the occurrence of medullary thyroid carcinoma in multiple endocrine neoplasia syndromes. An activated RET proto-oncogene germ-line mutation leads to the formation of familial medullary thyroid carcinoma and multiple endocrine neoplasia syndromes. The disease is transmitted in an autosomal dominant pattern and due to a very high penetrance (>95%) almost all carriers will be clinically affected with medullary thyroid carcinoma. The morphological manifestation of the disease is a multifocal C-cell hyperplasia leading to the increase of serum calcitonin (basal and stimulated with pentagastrin), the biochemical marker of medullary thyroid carcinoma. The coexistence of hyperparathyroidism, pheochromocytoma, multiple ganglioneuromas or marfanoid habitus in the patient with medullary thyroid carcinoma suggests the presence of the multiple endocrine neoplasia syndrome, MEN 2A or MEN 2B. The mutation at codon 634 of the RET gene is most common in MEN 2A, whereas mutation at codon 918 is found in the great majority of MEN 2B patients. The knowledge about the coexistence of medullary thyroid carcinoma in multiple endocrine neoplasia syndromes individual neoplasms to be detected early and the risk of neoplasia in family members to be determined.